Student’s Perception of Online Learning for Public Speaking Course - Ary Iswanto Wibowo; Sayyid Khairunas (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This research is aimed to find the perception of students on the speaking ability in Public Speaking class during pandemic Covid-19. By communicating to students who are from Public Relation majored, the researchers considered that speaking as a tool of communication should be done intensively. Therefore, within this pandemic teachers and students should change their learning methods from offline face to face to online face to face. The authors stated the problems that the students faced, they are perceptions and difficulties of online public speaking learning. A qualitative method had been used to analyze this case. The authors used the percentage of students as respondents to see the perceptions. The result of this research viewed that students disagree with the online Public Speaking Course. This amount consisted of 35,4% of total respondents that possessed in the second rank. While the first rank with the amount of 36,5% stated hesitation whether should be conducted online or offline. This also made authors and may other researchers to rethink about online Public Speaking Course. Perception, Public Speaking, Online